2023
DOI: 10.3390/pr11051567
|View full text |Cite
|
Sign up to set email alerts
|

Failure Analysis of the Crack and Leakage of a Crude Oil Pipeline under CO2-Steam Flooding

Abstract: This paper presents the failure analysis of the crack and leakage accident of a crude oil pipeline under CO2-steam flooding in the western oilfield of China. To analyze the failure behavior and cause, different testing, including nondestructive testing, chemical composition analysis, tensile property testing, metallographic analysis, and microanalysis of fracture and chloride stress corrosion cracking (SCC) testing, are applied in the present study. The obtained results showed that the pipeline under the insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(37 reference statements)
0
0
0
Order By: Relevance
“…Corrosion poses a serious threat, both externally and internally. External corrosion can result from factors such as oxygen and chloride in the external environment [6]. In contrast, internal corrosion may stem from substances such as hydrogen sulfide (H 2 S), carbon dioxide (CO 2 ), and organic acids present in the production fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion poses a serious threat, both externally and internally. External corrosion can result from factors such as oxygen and chloride in the external environment [6]. In contrast, internal corrosion may stem from substances such as hydrogen sulfide (H 2 S), carbon dioxide (CO 2 ), and organic acids present in the production fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al [23] studied the impact of Cl − on the stress corrosion of cold-deformed 316 L austenitic stainless steel in an H 2 S environment and found that the stress corrosion sensitivity of metal increases with the increase in Cl − concentration. Song et al [24] established the stress corrosion model of stainless steel by carrying out a chloride stress corrosion cracking test. They found that the existence of stress makes the passive film surface in the stress concentration area richer in chloride ions, thereby reducing the thickness, integrity, and pitting resistance of the passive film, and that SCC is the most destructive of all corrosion types.…”
Section: Introductionmentioning
confidence: 99%